2022
DOI: 10.1177/09673911221106684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blowing agents and curing temperatures on physical and mechanical properties of natural rubber foam for laminated floor tiles

Abstract: Falling on the floor has been one of the most common causes of breaking a bone. Falls in senior homes and care facilities can lead to immobility symptoms and treatments. Rubber flooring is a great alternative for fall protection. Thus, this study aimed to investigate the effects of organic blowing agents (dinitroso pentamethylene tetramine and azodicarbonamide) on the physical and mechanical properties of natural rubber foam used for laminated floor tiles. The curing temperatures were also examined in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…These findings align with the observations of Petdee et al, 27 who noted that increasing the blowing agent concentration leads to a reduction in the density of NR foam. This reduction in density offers various benefits in the manufacturing of foam‐based products.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings align with the observations of Petdee et al, 27 who noted that increasing the blowing agent concentration leads to a reduction in the density of NR foam. This reduction in density offers various benefits in the manufacturing of foam‐based products.…”
Section: Resultssupporting
confidence: 92%
“…The presence of higher amounts of CO 2 gas generated during the foaming process leads to a thinner cell wall thickness and consequently contributes to the reduction in weight of the SHNR foam. This effect is consistent with the findings of Petdee et al, 27 who observed that the volume fraction of the rubber compound doubled from 35% to 70% as the pore or cell sizes increased. As a result, the density of the foam decreased from 0.41 to 0.73 g/cm 3 .…”
Section: Foam Density and Porositysupporting
confidence: 93%
See 1 more Smart Citation